Improving learning and confidence through small group, structured otoscopy teaching: a prospective interventional study - Peng You; Saad Chahine; Murad Husein (Journal of Otolaryngology - Head and Neck Surgery, 2017)
Abstract Background Otologic diseases are common and associated with significant health care costs. While accurate diagnosis relies on physical exam, existing studies have highlighted a lack of comfort among trainees with regards to otoscopy. As such, dedicated otoscopy teaching time was incorporated into the undergraduate medical curriculum in the form of a small group teaching session. In this study, we aimed to examine the effect of a small-group, structured teaching session on medical students’ confidence with and learning of otoscopic examination. Methods Using a prospective study design, an otolaryngologist delivered an one-hour, small group workshop to medical learners. The workshop included introduction and demonstration of otoscopy and pneumatic otoscopy followed by practice with peer feedback. A survey exploring students’ confidence with otoscopy and recall of anatomical landmarks was distributed before(T1), immediately after(T2), and 1 month following the session(T3). Results One hundred and twenty five learners participated from February 2016 to February 2017. Forty nine participants with complete data over T1-T3 demonstrated significant improvement over time in confidence (Wilk’s lambda = .09, F(2,48) = 253.31 p < .001, η 2  = .91) and learning (Wilk’s lambda = 0.34, F(2,47) = 24.87 p < .001, η 2  = .66). Conclusions A small-group, structured teaching session had positive effects on students’ confidence with otoscopy and identification of otologic landmarks. Dedicated otoscopy teaching sessions may be a beneficial addition to the undergraduate medical curriculum.